Effect of electrode temperature on radiofrequency vacuum breakdown characteristics. (23rd November 2020) - Uimanov, I V; Shmelev, D L; Barengolts, S A
Abstract: The results of a numerical simulation of the heating of a microprotrusion on the surface of a copper electrode under the influence of radiofrequency electromagnetic fields, performed for different temperatures of the electrode, are presented. The calculation model describes self-consistently the thermal processes in the electron and phonon subsystems, the electron emission, and the effect of the space charge of emitted electrons. It has been shown that when the initial electrode temperature is increased to 1000 K, the time of heating of the surface microprotrusion to a critical temperature decreases by a factor of 1.5–1.9, namely, to values ranging from a few to tens of nanoseconds. This may significantly increase the probability of radiofrequency vacuum breakdown on the surface of the accelerating structure of an electron-positron collider.